2018
DOI: 10.1007/s13137-018-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

A greedy algorithm for nonlinear inverse problems with an application to nonlinear inverse gravimetry

Abstract: Based on the Regularized Functional Matching Pursuit (RFMP) algorithm for linear inverse problems, we present an analogous iterative greedy algorithm for nonlinear inverse problems, called RFMP_NL. In comparison to established methods for nonlinear inverse problems, the algorithm is able to combine very diverse types of basis functions, for example, localized and global functions. This is important, in particular, in geoscientific applications, where global structures have to be distinguished from local anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A Tikhonov-based regularization method, the so-called regularized functional matching pursuit algorithm [11,26,30], and its enhancement, the regularized orthogonal functional matching pursuit algorithm [29,39], will be used in a forthcoming work to solve these two problems numerically. Based on these methods, there exists a recently developed algorithm called the regularized weak functional matching pursuit algorithm which could improve and accelerate the numerical calculations of the inverse MEG and inverse EEG problem, see [20,21].…”
Section: Helmholtz Decomposition For Eegmentioning
confidence: 99%
“…A Tikhonov-based regularization method, the so-called regularized functional matching pursuit algorithm [11,26,30], and its enhancement, the regularized orthogonal functional matching pursuit algorithm [29,39], will be used in a forthcoming work to solve these two problems numerically. Based on these methods, there exists a recently developed algorithm called the regularized weak functional matching pursuit algorithm which could improve and accelerate the numerical calculations of the inverse MEG and inverse EEG problem, see [20,21].…”
Section: Helmholtz Decomposition For Eegmentioning
confidence: 99%
“…For practical purposes, we will give a short overview of the main principles of the RFMP algorithm, which is a regularization method for ill-posed linear problems, next. For more details on any IPMP, see, for example, [6,7,8,9,19,20,21,30,31,32,48]. For theoretical discussions of the IPMPs, we refer to this literature.…”
Section: Basic Principles Of Linear Ill-posed Inverse Problemsmentioning
confidence: 99%
“…Therefore, sophisticated algorithms need to be used to solve the problem of the downward continuation of satellite data. Previous studies showed that the (Regularized) Functional Matching Pursuit ((R)FMP), the (Regularized) Orthogonal Functional Matching Pursuit ((R)OFMP) as well as the latest (Regularized) Weak Functional Matching Pursuit ((R)WFMP) are possible approaches for this and other inverse problems, see, for instance, [3,6,7,8,9,17,19,21,20,29,30,31,32,48]. In the sequel, we will write Inverse Problem Matching Pursuit (IPMP) if we refer to either one of the mentioned algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation